Pengaruh Komposisi Media dan Konsentrasi Pupuk NPK Terhadap Pertumbuhan Tanaman Kaktus (Gymnocalycium damsii var.multiproliferum) - Denna Eriani Munandar; Nugraha Abdi Maulana (Berkala Ilmiah Pertanian, 2023)
ABSTRACT Cactus is a type of ornamental plant that is quite popular, so its development and reproduction is important. Cactus Gymnocalycium damsii var. multiproliferum can be propagated by shoots or saplings, but its growth is very slow. The success of cactus propagation is greatly influenced by the composition of the media and the nutrients provided. By choosing the planting media and providing the right nutrients, optimal growth of cactus saplings can be achieved. Malang sand is a planting medium with fine cavities that make it porous and light. NPK is a macro nutrient that is really needed to support plant growth and development. Research to obtain the right media composition and concentration of NPK fertilizer for the growth of Gymnocalycium damsii var multiproliferum cactus saplings was carried out using a factorial experiment using a completely randomized block design with 3 replications. The composition of the media is a ratio between soil: compost: Malang sand with 3 levels, namely: (1:1:1); (1:1:2) and (1:1:3) v/v. The concentration of NPK fertilizer consists of 4 levels, namely: 0; 1; 2 and 3 g/l. The results of the research showed that there was no interaction between planting media and konsentration of NPK fertilizer on growth of cactus . Concentration of NPK fertilizer 1 g/l gave the best results on plant diameter, plant height, shoot fresh weight, total fresh weight, root fresh weight, root length and root volume of the Gymnocalycium damsii var multiproliferum cactus sapling.